IKLAN LUAR RUANG : ANTARA KEPENTINGAN EKONOMI DENGAN KEPENTINGAN PUBLIK - Endarso Wicaksono; M. Edy Susilo; Puji Lestari (Jurnal Ilmu Komunikasi, 2008)
Now days, the outdoor advertising has been the effective way to promoted brand, prod- uct, or company. However, it’s could be negative with worst controlled by the government. In fact, Sleman economics importance is bigger than public importance. Economics importance belong to the government and advertising agency and public importance belong to society and target audience. This article tried to focus about economic importance and public importance connected.